2011
DOI: 10.1186/1471-2369-12-70
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroid hormone analogue and a leukotrienes pathway-blocker on renal ischemia/reperfusion injury in mice

Abstract: BackgroundAcute renal failure (ARF) is an important clinical problem with a high mortality and morbidity. One of the primary causes of ARF is ischemia/reperfusion (I/R). Inflammatory process and oxidative stress are thought to be the major mechanisms causing I/R. MK-886 is a potent inhibitor of leukotrienes biosynthesis which may have anti-inflammatory and antioxidant effects through inhibition of polymorphonuclear leukocytes (PMNs) infiltration into renal tissues. 3, 5-diiodothyropropionic acid (DITPA) have e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…According to our knowledge there was no data published Copyright © 2016 PCIJ 96 P a g e discussed the relationship renal ischemia reperfusion injury and effective role of GIT-27 on improved renal function following I/R model in rat. A number of published paper have investigated and confirmed that renal dysfunction during ischemia reperfusions related with inflammatory mediator's expression, including TNF-α and IL-1β [19]. Interestingly, we observed in this study that pretreatment with GIT-27 results in significantly reduction in cytokines with improvement in renal function.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…According to our knowledge there was no data published Copyright © 2016 PCIJ 96 P a g e discussed the relationship renal ischemia reperfusion injury and effective role of GIT-27 on improved renal function following I/R model in rat. A number of published paper have investigated and confirmed that renal dysfunction during ischemia reperfusions related with inflammatory mediator's expression, including TNF-α and IL-1β [19]. Interestingly, we observed in this study that pretreatment with GIT-27 results in significantly reduction in cytokines with improvement in renal function.…”
Section: Discussionsupporting
confidence: 70%
“…It is important to create novel medications to protect kidney from IRI [17]. Previous studies reported that expression of inflammatory mediators (TNF-α, IL-18) was higher following renal injury [18,19]. The present study investigated the GIT-27 to improve the renal function following ischemia reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…Additional effects included attenuation of the acute inflammatory response and reduction of myocardial infarct size (290), and improvement of maximal perfusion potential of the hypertrophied myocardium surviving a myocardial infarction (291). However, other studies reported side effects (292,293) or failed to obtain positive results with DITPA in similar settings (294,295).…”
Section: And Recommendation 29mentioning
confidence: 99%
“…However, unsuccessful administration of 3, 5diiodothyropropionic acid, 30min before renal IRI injury; may be due to short time course to exert preconditioning effect on oxidative stress [30] . PARP-1 activity and caspase-3 level were decreased in case of preconditioning with thyroid hormone as compared to IRI group either in acute renal IRI [4] or in the chronic kidney disease [31] .…”
Section: Discussionmentioning
confidence: 99%